Current status of genetic engineering in the fields of medicine, pharmacology and agriculture in China, Japan and Korea - Bích Hằng, Phạm Lê; Hà, Nguyễn Hải; Thu Hiền, Lê Thị (Vietnam Journal of Biotechnology, 2018)
Research and development (R&D) of genetic engineering in Asian countries, particularly in China, Japan and Korea, have been achieved great success and applied in many aspects of the social economic fields. In the area of medicine, these nations focus on studying the diagnosis of cancers, infectious, and hereditary diseases using molecular techniques based on PCR, and next generation sequencing; implementing clinical trials by gene therapy and improving prevention with innovative vaccines such as subunit or DNA vaccines. In addition, preparatory studies on human cells or embryos utilizing CRISPR/Cas9 genome editing technology have been undertaken in hopes of finding new treatments for genetic and cancer diseases. In the field of agriculture, many Asian countries have carried out R&D and approved genetically modified crops and produtcs for releasing into the environment and utilizing for food, feed and processing. The modified traits mainly are insect resistance, virus resistance, herbicide tolerance, drought tolerance, salinity tolerance, and increased nutritional value. In general, the level of development and application of genetic engineering in these nations has outstripped in Asia, but still underdevelopment state compared to the United States, Canada and several European countries. Therefore, each country should have appropriate policies and investments to promote the application of advanced biotechnologies in the world in order to improve the quality of human life